Business plan for the establishment of a company developing custom electronics - Mikešová, Jana (2018)
The bachelor thesis focuses on the design of a business plan for the establishment of a company developing custom electronics. The aim of the thesis is to collect materials that are useful for starting the real business. The business plan answers the questions whether the project is feasible and under what conditions, whether it is competitive, what are the appropriate forms of promotion, what are the risk factors, what is the amount of initial investment and what is the payback period.The following analytical methods are used to process the business plan: SWOT analysis, customer analysis, including questionnaire survey, competition analysis, supplier analysis, marketing mix, revenue distribution analysis, cash-flow analysis, break even point analysis, risk analysis, net present value, internal rate of return, payback period. The conclusion of the bachelor thesis evaluates the whole project as feasible, competitive and able to generate sufficient financial resources to be economically sustainable. The most effective forms of promotion are optimized websites and word of mouth. The highest risk is the exaggerated financial plan and lower than expected sales. The initial investment is assessed as sufficient with payback period between the first and the second year in all considered development options.